PENGARUH NILAI-NILAI TUNJUK AJAR MELAYU UNTUK MENINGKATKAN HUBUNGAN SOSIAL SISWA MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 4 PEKANBARU - Ajrina Amri Yunita; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to examine the tunjuk ajar melayu teaching point values to improve student social relations at SMP Negeri 4 Pekanbaru. This type of research is quantitative research with experimental methods using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study is a scale that measures students' social relations consisting of 40 items before validation, and after validation 30 items are obtained valid items with validity between 0.358-0.793 and reliability 0.926. The subjects of this study were 9 students who were identified as having low social relations. The data analysis technique used is non-parametric statistical techniques using the Rank Spearman test. The results of the study prove the accepted research hypothesis. For that from the Spearman Rank test results obtained r = 0.778 while the correlation coefficient r2 is 0.61. Thus there is a tunjuk ajar melayu teaching point values on social relations of students by 61% in SMP Negeri 4 Pekanbaru. From the Wilcoxon test results obtained (Asymp.Sig) 0.018 <0.05, it can be concluded that there are differences in social relations of students before and after the treatment of tunjuk ajar melayu teaching point values, as evidenced by an increase in each indicator of students' social relations.Key Words: Social Relation, Tunjuk Ajar Melayu, Group Guidance